2022
DOI: 10.1002/aelm.202201086
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin, Graphene‐in‐Polyimide Strain Sensor via Laser‐Induced Interfacial Ablation of Polyimide

Abstract: Laser‐induced graphene sensors have attracted considerable interest in various fields; however, the low sensitivity and conformability limit their further applications in measuring soft, large deformable structures. Here, an innovative method of interface ablation is presented to convert the interfacial polyimide into graphene by nanosecond ultraviolet laser (308 nm). Significantly different from the traditional laser surface ablation, interface ablation demonstrates its unique capacity to produce high‐quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…The flexible strain sensor exhibited outstanding performance, as illustrated in Table 1 . This sensor demonstrated superior sensitivity compared to the sensors utilizing alternative conductive materials and fabrication processes [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. The sensor fabricated using four scans exhibited even higher sensitivities, reaching up to 11.5 in the range of 0.0% to 4.2%, and as high as 142.7 in the range of 4.2% to 9.0%, which is more visually represented in Figure 4 c. This indicates a more pronounced change in relative resistance compared with sensors of the first two categories.…”
Section: Resultsmentioning
confidence: 99%
“…The flexible strain sensor exhibited outstanding performance, as illustrated in Table 1 . This sensor demonstrated superior sensitivity compared to the sensors utilizing alternative conductive materials and fabrication processes [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. The sensor fabricated using four scans exhibited even higher sensitivities, reaching up to 11.5 in the range of 0.0% to 4.2%, and as high as 142.7 in the range of 4.2% to 9.0%, which is more visually represented in Figure 4 c. This indicates a more pronounced change in relative resistance compared with sensors of the first two categories.…”
Section: Resultsmentioning
confidence: 99%
“…In 2018, Alexandre first reported that a fourfold reduction in ablation depth thickness and a doubled improvement in spatial resolution could be achieved by using a UV laser with a wavelength of 355 nm (pulse duration of 1 µs) [41] . After that, lasers with other wavelengths were widely used to prepare LIG, including 1064 nm (continuous wave) [87,88] , 532 nm (continuous wave) [82,89] , 450 nm (continuous wave) [80,90,91] , 405 nm (pulse duration of 10~50 ms) [86,92,93] , 355 nm (pulse duration of 10 ps) [83] , 343 nm (pulse duration of 220 fs) [94,95] , and 308 nm (pulse duration of 20 ns) [96] , indicating that the preparation of LIG is independent of laser sources. Compared to laser sources with long pulse widths (continuous wave, millisecond, microsecond, and nanosecond), ultrafast lasers (pulse duration of picosecond and femtosecond) enable higher processing resolution due to the smaller heat-affected zone.…”
Section: Diversity Of Laser Sourcesmentioning
confidence: 99%
“…Existing LIG processing techniques primarily focus on surface irradiation, thereby requiring additional encapsulation procedures after LIG fabrication. Unfortunately, this process often causes damage to the LIG due to its inherently porous and delicate features [ 25 ]. More importantly, this surface lasing process leads to the inevitable exfoliation and oxidation of the as-formed graphene, negatively impacting the integrity and electrical property of LIG [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%